Meningkatkan Hasil Belajar Siswa pada Muatan PKN melalui Model Pembelajaran Permainan Di Kelas I SDN 126/IX Sungai Beluru - Farida Sudarma (Jurnal Gentala Pendidikan Dasar, 2020)
The purpose of this school action research is to obtain data and information Efforts to improve student learning outcomes in PKN subjects through game learning models in Class I SDN 126 / IX Sungai Beluru in the first semester of the academic year 2017/2018. This type of research is a classroom action research (CAR) of two cycles. Each cycle consists of four stages: planning, implementing, observing, reflecting. The subject of the action referred to in this study were students in class I SDN 126 / IX Sungai Beluru, which amounted to 20 students. while the participants involved in this study were class teachers and other colleagues. The data obtained are quantitative and qualitative data. Data collection methods used in classroom action research include tests, observations, and documentation and are analyzed using the percentage and data reduction techniques. Based on the results of research that has been done for two cycles, the results of all discussions and analyzes that have been done can be concluded that the learning model of the game can make students feel easier to understand the material delivered by the teacher and can improve student learning outcomes in learning Civics in Class I SDN 126 / IXSungai Beluru with the act of giving gifts